Experimental investigations on the combustion of lithium particles in CO2 and CO2-N2 mixtures. (1st July 2017) - Schiemann, Martin; Fischer, Peter; Bergthorson, Jeffrey M.; Schmid, Guenter; Taroata, Dan
Graphical abstract: Highlights: Lithium particles were burned in CO2 -containing atmospheres with nitrogen dilution. Optical and sampling methods were used to characterize combustion time scales. In nitrogen-diluted CO2 atmospheres, the formation of Li2 CO3 is retarded. Combustion temperature decreases with CO2 partial pressure. Abstract: Energy cycles based on lithium combustion have been proposed recently and provide an option to combine the benefits of high-density energy storage with carbon-free production of heat, power and chemicals. Knowledge on efficient combustion processes for lithium is limited. In the current work, combustion experiments for single lithium particles ( dp  = 10–250 µm) burning in CO2 and three different CO2 -N2 mixtures are carried out using a laminar flow drop tube reactor. In order to determine combustion times, temperatures and burnout constituents, the burning particles are investigated using three different measurement techniques: a reflex camera, a high speed two-color pyrometer and a sampling probe to collect burnout samples. The results confirm the existence of two combustion stages, which have been observed before: gas-phase combustion and surface reaction. As detailed investigations show, the duration of the gas-phase combustion is approximately ten times shorter compared to the surface reaction. In addition, the burnout times of both combustion stages increase clearly for lower CO2 partial pressures. The reduction of the CO2 partial pressure leads to lower combustion temperatures as well as the production of less Li2 CO3 and more Li2 O, while no nitrogen compounds are formed.